ISLAM DI NEGERI MATAHARI TERBIT (Suatu Kajian Histori dan Akselerasi) - Andi Muhammad Akmal (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2019)
The land of the rising sun is known by the nuances of Islamic values ​​reflected in the attitudes and behavior of the people. This study aims to explore the history of the growth and development of Islam in the land of the rising sun and the challenges faced by Muslims and the impact of Islamic teachings on the behavior and character of society in Japan. This study is qualitative descriptive with a historical sociological approach. The results of the study show that Islam in Japan is growing rapidly as evidenced by the construction of mosques, the formation of Muslim associations and currently the government promotes halal tourism. This works because of strong tolerance. The impact of Islamic teachings appears on the character of Japanese society. Nevertheless Muslims still need preachers who are able to speak Japanese to improve religious understanding.